What Does Self-control Look Like? Considerations about the Neurobiology of Temperance and Fortitude - Mullins, Andy (Conatus - Journal of Philosophy, 2025)
Our subject is the neurobiological characteristics of virtuous emotional responses and their integration into character. Drawing raw material from the self-reported thoughts and actions of Dr Takashi Nagai, present in Nagasaki at the time of the atomic bomb, our methodology is to conduct a highly granular examination of one specific moment where his self-control is greatly tested. This permits us then to offer an analysis of the neurobiological processes, pathways, and systems that underpin the management of emotional reactions, and in effect, draw insight into the neurobiology of virtues of temperance and fortitude, understood from an Aristotelian-Thomistic perspective. The neurobiological considerations are preceded by discussion of philosophical prerequisites founded on a Thomistic metaphysics of participation. In conclusion we offer some thoughts about the benefits of neurobiological investigations in relation to character and the aptness of the development of virtue for human beings.